Tungsten Trioxide (Wo3) Based Photo Electro Chemical (Pec) Cell In The Presence of N Methyl Formamide - T.V. Reddy; K. Saritha; S. Sirisha; Ch. Rajani (International Journal of Psychosocial Rehabilitation, 2020)
TUNGSTEN TRIOXIDE (WO3) is an n-type semiconductor which may be used as photo sensitive electrode and photo catalyst in the presence of organic substrates.WO3photoelectrochemical (PEC) cell is constructed in the presence of N-methyl formamide (NMF). In oxygen atmosphere, WO3electrode produces cathodic photocurrent which is attributed to the reduction of O2 and anodic photocurrent is due to oxidation of NMF in the presence of N2. A suitable mechanism is proposed for the electrode reactions.